Microarrays. The bridges in the knowledge of mental retardarion diagnosed in childhood - Márquez González Horacio; Márquez Flores Horacio; Camarillo Blancarte Leyla (Instituto Nacional de Pediatría, 2014)
Mental retardation (MR), is a common neurological condition in children. Its etiology may be genetic or environmental. In the first case, all the disorders that cause it have not been identified and a considerable number of patients do not have an accurate diagnosis. Microarrays are derived from comparative genomic hybridiza- tion (CGH), which can determine sites of deletions, insertions or translocations. This technique has made it possible to determine chromosomal syndromes not previously described such as: 17q21.31 deletion, deletion 15q24 or 1q21 deletion. It can be done in large populations or be individualized. The intro- duction of this technique has begun to resolve doubts regarding monogenic or polygenic RMI.